2015
DOI: 10.1007/s13187-015-0903-3
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Cancer Awareness and Knowledge: Is It the Same? Exploratory Study in a Mixed-Gender Population

Abstract: Testicular cancer (TC) is among the most common malignancies in the young male. Awareness plays an important role, because delay in diagnosis affects outcome. Testicular self-examination (TSE) is controversial, but recent evidence shows some cost benefits in performing this exam versus a late-stage diagnosis. The aims of this study are to determine and compare awareness for TC and TSE in males and females with the actual knowledge to this disease in an academic population. An exploratory study using an online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
1
12
0
2
Order By: Relevance
“…According to a number of literature sources on testicular cancer awareness, the level of knowledge among the young men is relatively low [10,11]. The study conducted among men in Lubelskie Province leads to a similar conclusion.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…According to a number of literature sources on testicular cancer awareness, the level of knowledge among the young men is relatively low [10,11]. The study conducted among men in Lubelskie Province leads to a similar conclusion.…”
Section: Discussionmentioning
confidence: 59%
“…Jeden mężczyzna (0,8%) przyznał, że w jego bliskiej rodzinie wystąpił przypadek tego nowotworu. DYSKUSJA W nawiązaniu do licznych źródeł literatury, wiedza na temat nowotworu jądra w populacji młodych mężczyzn jest stosunkowo niska [10,11], co potwierdziło badanie przeprowadzone wśród młodych mężczyzn w wojewódz-twie lubelskim. Świadomość tej tematyki wydaje się być niewystarczająca, co wnioskować można z samooceny osób poddanych badaniu, a także ewaluacji opartej na wynikach kwestionariusza.…”
Section: Pielęgniarstwo XXI Wiekuunclassified
“…A low level of awareness of young age as a risk factor for TC was revealed, which is particularly disappointing. Various reports have indicated that young male students are unaware of being in the age-risk group for TC, which is the most common neoplasm in 15-35 year age group [14,24,25]. Presumably, young men are not very conscious of cancer and their perception of malignant pathologies is associated only with older people [26].…”
Section: Discussionmentioning
confidence: 99%
“…Surveys conducted by various researchers also show that the percentage of correct answers concerning the early symptoms of TC uctuates and seems to be unsatisfactory. Braga et al found that only about 42% of Portuguese male respondents indicated to the most common TC signs and symptoms correctly [24]. Roy et al documented that less than 30% of Irish men properly recognized the rst symptoms of the disease [14].…”
Section: Discussionmentioning
confidence: 99%
“…For the majority of patients, however, symptoms are insidious and non-specific, and an enlarged lymph node or other mass is usually the first diagnostic sign [55]. As with breast [56, 57] and testicular [58–60] cancer, socio-economic factors may lead to cultural and educational differences causing delay before presenting with a lump. These delays may contribute to late or emergency presentation.…”
Section: Discussionmentioning
confidence: 99%